The magic kerchief - Larson, Kirby; Litzinger, Rosanne (New York : Holiday House, 2000)
Sharp-tongued and lonely Griselda gets a magic kerchief from a mysterious stranger, and when she wears it she can speak only kind words to the people she meets.
2.6
K-3
K-3
School Library Journal
Publisher's Weekly
Booklist
Keywords: Fairy tales; Fairy tales